2011
DOI: 10.1016/j.ophtha.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The Child Self-Refraction Study

Abstract: Objective To compare visual and refractive outcomes between self-refracting spectacles (Adaptive Eye-care, Ltd, Oxford, UK), noncycloplegic autorefraction, and cycloplegic subjective refraction. Design Cross-sectional study. Participants Chinese school-children aged 12 to 17 years. Methods Children with uncorrected visual acuity ≤6/12 in either eye underwent measurement of the logarithm of the minimum angle of resolution visual acuity, habitual correction, self-refraction without cycloplegia, autorefract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 38 publications
13
30
1
Order By: Relevance
“…A study performed in rural Southern-India found that >65% of a population with high rates of RE correctable with glasses were not wearing them due to inadequate access [ 2 ]. As such, the World Health Organization and the International Agency for the Prevention of Blindness have made the treatment of RE a priority in their VISION 2020 global initiative [ 3 ]. In 2011, however, many countries in sub-Saharan Africa were not on target to achieve goals of 20 refractionists per million population due to a smaller and more unevenly distributed eye health workforce [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed in rural Southern-India found that >65% of a population with high rates of RE correctable with glasses were not wearing them due to inadequate access [ 2 ]. As such, the World Health Organization and the International Agency for the Prevention of Blindness have made the treatment of RE a priority in their VISION 2020 global initiative [ 3 ]. In 2011, however, many countries in sub-Saharan Africa were not on target to achieve goals of 20 refractionists per million population due to a smaller and more unevenly distributed eye health workforce [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…USee allows a user to self-refract and receive a pair of plastic eyeglasses on site with pop-in best-sphere lenses, an improvement over ready-made spectacles used in some programs. Although USee can only provide SE correction, prior studies have shown that ready-made eyeglasses of this type were still well tolerated and highly valued [ 3 , 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This self-refraction technique is a potential solution to the shortfall of eye-care professionals in developing countries, as it enables an individual to self-adjust the lens power to arrive at an adequate level of vision. These novel self-refracting spectacles have been shown to achieve good vision both in adults16,31 and children 9,32…”
Section: Self-adjustable Spectaclesmentioning
confidence: 99%
“…Self-adjustable spectacles (liquid filled) have been tried in school-aged children in the USA36 and the People’s Republic of China,9,32 and in older populations in the USA,16 South Africa,31,37 Ghana,31,37 Malawi,31 Nepal,31 and Nicaragua 16. Cycloplegic refraction was considered the gold standard in the studies in the USA36 and the People’s Republic of China 9,32. It was observed that nearly 92% of the children in Boston, USA;36 85% in Guangzhou, People’s Republic of China;9 and nearly 97% in Chaoshan, People’s Republic of China,32 were able to attain a vision of 6.0/7.5.…”
Section: Self-adjustable Spectaclesmentioning
confidence: 99%
See 1 more Smart Citation